Managing extreme financial risk : strategies and tactics for going concerns - Paul, Karamjeet (Academic Press, 2014)
Managing Extreme Financial Risk addresses the need for better management strategies in light of increased market risk and volatility in financial institutions' revenue models. Top officials from the financial and regulatory industries point to real corporate issues, showing how institutions react to financial crises. From first-hand experiences, they explain how effective sustainability management does not just prevent being blindsided; it also leads to proactive solutions that enhance an institution's strength to weather a sudden financial crisis, add significant shareholder value, and reduce systemic risk. Readable, coherent, and logical, Managing Extreme Financial Risk shows how extreme risk needs to be handled when the cost of being wrong means the difference between life and death of the institution. Based on the firsthand experiences and perspectives of senior-level executives Concentrates on extreme risk, when the cost of being wrong is not the loss of profits, but the death of the institution Written to be easily understood without algorithms, models, and quants.